Revitalizing Environment Order against Spatial Outside in Cikapayang River Park Area - Theresia Pynkyawati; Friska Hera Yulinda; Fajar Nurdarajat; Yuda Septiyagi (Department of Architecture Universitas Muhammadiyah Jakarta, 2020)
Cikapayang River Park’s pedestrian area that’s less organised from ecological and environmental side. New cikapayang River Park aims to provide comfortable public space while utilizing river as mutually interconnected supporting component. Outer space Environmental order includes environmental order against outer order, Merdeka street corridor which’s restricted by Cikapayang river, Bandung City Hall, Cikapayang River and Merdeka street, also Cikapayang river purification. Previously, Cikapayang River Park’s a single function as sidewalk, after revitalization, it has additional function as better public open spaces also Cikapayang river restoration became basis of this research. Analytical descriptive method used as methodology through direct survey to Cikapayang River Park from changing environmental order into public open space, then associating survey results conditions, before and after revitalizing to literature as basis of theories and river purrification. Analysis results showed impact of revitalization on Cikapayang River Park’s creating positive outdoor space, so it can accommodate the people activities.